2020
DOI: 10.1016/j.childyouth.2020.105535
|View full text |Cite
|
Sign up to set email alerts
|

Perceived usability evaluation of Microsoft Teams as an online learning platform during COVID-19 using system usability scale and technology acceptance model in India

Abstract: Highlights Measuring the perceived usability of online learning platforms is an important issue in times of COVID-19 as now the education delivery is “online only” The prevalence of a digital divide in terms of the consumption platform (smartphones vs. laptops) does not have any effect on the perceived usability of the online learning platform. The visually different approaches followed by the HCI and IS research community towards usability evaluation (in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
237
0
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 329 publications
(269 citation statements)
references
References 66 publications
10
237
0
22
Order By: Relevance
“…Focusing specifically on the educational aspect, the technical factors are an important issue to be considered in the COVID-19 era. This is because current research has shown that there exists a great diversity among the Indian students in terms of the type of devices owned (smartphones/laptops/desktops used for the purpose of online learning) or even the speed of their Internet connections (Kapasia et al, 2020;Pal & Vanijja, 2020). Further, the viewing experience depends on the type of device used (specifically on the screen size) (Pal & Vanijja, 2017a, 2017bZhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Focusing specifically on the educational aspect, the technical factors are an important issue to be considered in the COVID-19 era. This is because current research has shown that there exists a great diversity among the Indian students in terms of the type of devices owned (smartphones/laptops/desktops used for the purpose of online learning) or even the speed of their Internet connections (Kapasia et al, 2020;Pal & Vanijja, 2020). Further, the viewing experience depends on the type of device used (specifically on the screen size) (Pal & Vanijja, 2017a, 2017bZhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One of the studies has shown that Moodle was one of the effective platforms that have been used within dental schools where students have shown a positive impression [10]. A similar study by [11] has adopted a survey among university students that measures the usability of Microsoft Teams as a reference platform using the (Technology acceptance Model) TAM model. It concludes that the effectiveness of these platforms is highly evident, especially in developing countries where perceived usability is highly evident.…”
Section: Introductionmentioning
confidence: 99%
“…Malgré la puissance indéniable de leurs fonctionnalités, les ENA ne suffisent pas à combler les besoins des étudiant•es, notamment pour avoir des interactions et offrir « des conseils [ou de l'] aide » ou encore « pour se répartir les tâches et aider les élèves en difficulté ». On notera que, dans le cadre des mesures alternatives d'enseignement liées à la COVID-19, des plateformes comme Microsoft Teams et Google Classroom semblent avoir été grandement sollicitées par les institutions d'enseignement, notamment car l'on y retrouve des fonctionnalités que l'on voiyait sur des médias sociaux, comme la possibilité d'organiser des discussions de groupe(Pal et Vanijja, 2020). Des perspectives de recherches s'ouvrent sur la façon dont sont mobilisés ces espaces hybrides par les étudiant•es, par exemple dans le cadre de groupe d'études.…”
unclassified